UTILIZATION OF ARTEMIA IN THE LAMINING OF CAT FISH, Clarias sp. IN KARANG BESUKI URBAN VILLAGE - Agoes Soeprijanto; Pratama Deffi Samuel; Muhammad Fakhri (Journal of Innovation and Applied Technology, 2017)
AbstractThe main problem in catfish hatchery is low productivity and survival rate (SR). The aim of this work was to evaluate the application of artemia in catfish hatchery. Artemia was administered to 100,000 catfish larvae for 3 days with the total of 602 gr. The results showed that 70,000 catfish juveniles with size of 2-3 cm were obtained under artemia application. The survival rate of this study was 70%. It can concluded that probiotic application was able to improve the survival rate and the feed conversion ratio in catfish culture.